Implementación de normas de seguridad en la red lan del laboratorio de desarrollo de software de la Universidad Técnica de Cotopaxi extensión La Maná en el periodo abril – agosto 2015 - Suárez Ledesma, Juan Jesús (2016)
At the present time we are in a developed world where communication and information are the most delicate elements of organizations, we are in the area where computer networks are media that dominate all aspects of daily life both firms and individuals, so that networks have become a key element in establishing relationships with other organizations worldwide, many institutions in the world have detected security problems on their networks, reason for mitigate these problems are investing in technology to enable it to provide security for their information assets, it is not made solely to invest in technology....